Frequency of Hyponatremia and Its Effect on Complications in Decompensated Chronic Liver Disease (DCLD) - Toqeer Ahmad; Amara Tassudaq; Noreen Bukhari; Hamza Salman; Rabail Naseer; Ikram ul Haq (Journal of University Medical & Dental College, 2026)
BACKGROUND & OBJECTIVE: Hyponatremia, an electrolyte imbalance, is prevalent in decompensated chronic liver disease (DCLD) and is linked to an increased risk of complications, including hepatic encephalopathy, ascites, hepatorenal syndrome, and variceal bleeding. The study aims to assess the frequency of hyponatremia and its impact on various complications in patients with DCLD. METHODOLOGY: A cross-sectional study was conducted on 120 DCLD patients aged 15-75 years at Allama Iqbal Memorial Teaching Hospital from January to June 2023. The sample size of 120 patients was stratified using the Child-Pugh classification, and complications were assessed, including ascites, hepatic encephalopathy, hepatorenal syndrome, variceal bleeding, and spontaneous bacterial peritonitis. The data analysis was conducted using SPSS version 23. Chi-square test was applied, and a p-value of ≤ 0.05 was considered statistically significant. RESULTS: The frequency of hyponatremia was 40%, with 48 patients affected. Complications were more common in patients with hyponatremia, including ascites (80.6% in males, p = 0.000; 94.1% in females, p = 0.005), hepatic encephalopathy (45.2% in males, p = 0.026), and hepatorenal syndrome (9.7% in males, p = 0.016). Variceal bleeding was significantly associated with hyponatremia (22.6% in males, p = 0.004). CONCLUSION: Hyponatremia is a frequent and clinically significant complication in DCLD, associated with higher morbidity and mortality. Early detection and management are crucial for improving patient outcomes.